2017
DOI: 10.18488/journal.2.2017.79.404.420
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterisation of Ralstonia Solanacearum Strains of Tomato Wilt Disease from Maseno, Kenya

Abstract: Article HistoryRalstonia solanacearum (E.F. Smith) Yabuuchi, is the cause of bacterial wilt of tomato and one of the most severe pathogens of solanaceous crops with a very wide host range. There is little information on R. solanacearum strains in Maseno region in Kenya despite the fact that bacterial wilt of tomato is of economic importance. The objective of this study was to isolate the strains of R. solanacearum of tomato and characterize morphologically and biochemically Ralstonia solanacearum races and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Similarly, morphological characteristics of the re-isolated bacterium from these test plants were identical to those of the original pathogen on TZC media. Similar results were reported in other studies ( Rahman et al, 2010 , Popoola et al, 2015 , Khasabulli et al, 2017 , She et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, morphological characteristics of the re-isolated bacterium from these test plants were identical to those of the original pathogen on TZC media. Similar results were reported in other studies ( Rahman et al, 2010 , Popoola et al, 2015 , Khasabulli et al, 2017 , She et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…nov. characteristics on this medium as described by Kelman (1954) . Both the Gram stain and KOH solubility tests confirmed that the isolated bacterium was gram negative and this was in agreement with the research findings by Rahman et al, 2010 , Khasabulli et al, 2017 , She et al, 2017 . The isolated bacterium oxidized all the disaccharide sugars and hexose alcohols.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The H 2 O 2 is a reactive oxygen species (ROS) that can cause plant cell death because of the carcinogenic effects at the high cellular level of H 2 O 2 (Khandaker et al, 2020). The catalase test suggested that these bacteria contain catalase that could neutralize hazardous forms of oxygen metabolites, such as H 2 O 2 into oxygen and water (Khasabulli et al, 2017). However, excessive accumulation of water in the vessels will cause hyperhydricity of the plant tissue, causing oxidative stress and oxygen depletion in the cells (Ziv, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Plant height was measured as described by Khasabulli et al (2017), from soil level to the upper point of the terminal bud of the seedling using a meter rule every fourteen days up to the end of the experiment. Two randomly selected plants in each pot were tagged and measured.…”
Section: Plant Heightmentioning
confidence: 99%